The smaller, the better? The size effect of alginate beads carrying plant growth-promoting bacteria for seed coating. (17th February 2016) - Berninger, Teresa; Mitter, Birgit; Preininger, Claudia
Abstract: A range of lab-scale methods for encapsulation of plant growth-promoting bacteria in alginate beads intended for seed coating was evaluated: contact-spotting, extrusion through syringe with/without vibration, ejection by robotic liquid handler, extrusion by centrifugal force and commercial devices (nanodispenser, aerodynamically assisted jetting, encapsulator). Two methods were selected based on throughput (encapsulator: 1.5–5 mL/min; syringe with subsequent pulverisation: 5 mL/min). Four bead sizes (55 ± 39 μm, 104 ± 23 μm, 188 ± 16 μm and 336 ± 20 μm after lyophilisation) were produced. Bacterial viability, release, bead morphology, seed surface coverage and attrition were investigated. Release from the smallest bead size was approximately 10 times higher than from the largest. Seed surface coverage was highest (69 ± 3%) when alginate beads produced with nozzle size 80 μm were applied. Pulverised macro-beads are an alternative option, if high throughput is top priority.